Processo de estratégia: um estudo de caso em uma empresa fabricante de equipamentos de telecomunicações - Shintani, Edson Kiyoshi (2011)
Research on the strategy process seeks to answer complex questions of how strategies are formed, implemented and reviewed, capturing the complex and dynamic relationship between the content of the strategy and its context of use. Despite of the vast literature, relatively little is known about how the processes actually affect the strategy, making the strategy process work more about processes than actually strategy. This study aims to contribute to the knowledge of business strategy, using the strategy as practice as a way to observe the phenomenon of strategy process in the field and exploring the strategy practice in the organization. This research is based on an exploratory case study of a single telecommunication equipment manufacturer, a global technology leader in the segments where it operates, identifying changes in the strategy process occurred after the change of CEO and the results observed in the practice of strategy. Some of the strategic changes occurred are investigated: realignment of solutions to new business, focus on content for cellular networks to capture value and internationalization. Some relevant market information from international institutions is used about Internet growth, infrastructure of communications and mobility. From academy, concepts were used to enlarge the understanding of the context and analysis of external environment of the organization: information rules, Internet and transaction costs, value chain, game theory and evolutionary speed of the industry; and internal environment: strategy, its formation and practice, strategic planning, value of innovation, internationalization and structure influence. Analyzing the presented above, increased importance of strategy subject and complexity were realized in industries somehow related to the Internet, suggesting, for example, alternative interpretations of the relationship between strategy and organizational structure.